Providing Multidimensional and Geographical Integration Based on a GDW and Metamodels - do Nascimento Fidalgo, Robson; Times, Valéria Cesário; da Silva, Joel; de Souza, Fernando da Fonseca; Salgado, Ana Carolina (Journal of Information and Data Management, 2010)
Data Warehouse (DW), On-Line Analytical Processing (OLAP) and Geographical Information System (GIS) are tools for providing decision-making support. Much research is aimed at integrating these technologies, but there are still some open questions, particularly regarding to the design of spatial dimensional schemas of Geographical DW (GDW) and the models for providing a semantic integration among the metadata of such technologies. To perform this task we are based on the Geographical On-Line Analytical Processing Architecture (GOLAPA), to propose 1) the framework GeoDWFrame, which is based on the star schema and has been specified as guidance for designing geographical dimensional schemas and 2) a pair of MOF based metamodels, namely: Geographical Analytical Metamodel (GAM) and Geographical Multidimensional Metamodel (GeoMDM), which, respectively, provide the modelling of analytical and spatial applications and the integration of the CWM OLAP and GAM metamodels. We have also developed a case study, where the GeoDWFrame and these metamodels are applied.